PREDATORY EFFICIENCY OF CHEILOMENES SEXMACULATA (FABRICIUS) (COLEOPTERA: COCCINELLIDAE) AGAINST APHIS CRACCIVORA KOCH ON VARIOUS HOST PLANTS OF FAMILY FABACEAE - Rakhshan, Rakhshan; Ahmad, Md. Equbal (European Scientific Journal, ESJ, 2015)
Coccinellid beetles due to high foraging performance, immense predatory potential and high reproductive efficacy, they possess the potential to be effectively employed in biological control programmme for controling several destructive insect such as white flies, coccids, thrips, mites, adelgids, psyllids, mealy bugs and scale insects. Cheilomenes sexmaculata is predominent species against Aphis craccivora in different localities of Bihar on agricultural and horticultural plants (Ahmad et al., 2012). The knowledge of predatory efficiency plays an important role in mass rearing and its utilization in management programme. The effect of host plants quality on the development and feeding potential of each instars and adult stages of C. sexmaculata was investigated. The greater consumption of A. craccivora was observed by both adult and grubs on P. sinensis (717. 0±10.33 aphids) followed by L. purpureus (655.8±18.19 aphids), V. radiata (620.8 ± 5.04 aphids) and V. mungo (546.2±12.39 aphids). The larval and adult stages of C. sexmaculata consumed more A. craccivora on P. sinensis than other host plants. Many intrinsic characteristics of plants such as nutritional value, secondary chemicals, and morphology can influence the feeding potential of predators. Thus, in the present investigation more feeding potential was observed on P. sinensis is due to high nutritional values of the host plants.